Manajemen Kepala Madrasah dalam Meningkatkan Prestasi Belajar Siswa - Abdul Rahim (Center for Religious Studies and Social Empowerment Foundation, 2022)
This article discusses the management of the Head of Private Madrasah Nurul Iman Jambi City in improving student achievement. The main problem studied is why the management of the Madrasah Principal has not been able to improve student learning achievement at the Nurul Iman Private MTs, Jambi City? This research is a descriptive qualitative research that reveals, finds and explores information about the management of Madrasah Principals in improving student achievement. This study found that the increase in student achievement at MTs Swasta Nurul Iman Jambi City has not been managed optimally due to budget constraints and the weakness of the coaches' skills in implementing existing learning achievement improvement programs. However, there are still supporting factors for school principals in developing student learning achievement, for example the existence of a system of openness among school members in fostering learning achievement and the existence of programs that focus on certain learning achievements. Meanwhile, the obstacles encountered were the low compensation for teacher work, the discipline of the coaches was still weak, and interpersonal communication between the coaches and the principal was still not effective. Artikel ini membahas tentang manajemen Kepala Madrasah Swasta Nurul Iman Kota Jambi dalam meningkatkan prestasi belajar siswa. Persoalan utama yang dikaji adalah mengapa manajemen Kepala Madrasah belum mampu meningkatkan prestasi belajar siswa di MTs Swasta Nurul Iman Kota Jambi? Penelitian ini merupakan penelitian kualitatif deskriptif yang mengungkapkan, menemukan dan menggali informasi tentang manajemen Kepala Madrasah dalam meningkatkan prestasi belajar siswa. Penelitian ini menemukan bahwa peningkatan prestasi belajar siswa di MTs Swasta Nurul Iman Kota Jambi belum dikelola secara optimal karena keterbatasan anggaran dan lemahnya kecakapan pembina dalam mengimplementasikan program peningkatan prestasi belajar yang ada. Namun demikian, tetap ada faktor pendukung bagi Kepala Sekolah dalam mengembangkan prestasi belajar siswa, misalnya adanya sistem keterbukaan di antara warga sekolah dalam membina prestasi belajar serta adanya program yang fokus pada prestasi belajar tertentu. Sedangkan kendala yang ditemui adalah kompensasi kerja guru yang masih rendah, disiplin pembina masih lemah, dan komunikasi antarpersonal pembina-Kepala Sekolah masih belum efektif.